Calculation of displacements and stresses in laminated glass beams under dynamic loadings using an effective Young modulus. (2017) - Aenlle, Manuel L.; Pelayo, F.; Ismael, G.
Abstract: Laminated glass is a sandwich element that consists of two or more sheets of monolithic glass with one or more interlayers of a polymer that usually show viscoelastic behavior. In recent years, the concept of effective thickness has been proposed to calculate displacements and stresses in laminated glass elements subject to static loadings. The method consists of using a monolithic model with the same length and boundary conditions and subject to the same loading as the laminated glass model but with an effective thickness such that both models (the monolithic and the laminated one) provide the same displacements and stresses as the laminated glass beam. This technique allows to save time in the calculation of the laminated glass elements subject to dynamic loadings compared with the layered finite element models which are very high time consuming because many small 3D elements are needed to model accurately all the layers of the sandwich element and because the core usually shows a time and temperature dependent behavior. In this paper, a technique to estimate displacements and stresses in the frequency domain in laminated glass beams subject to dynamic loadings is proposed based on the effective Young modulus concept. Both the effective thickness and the effective Young modulus can be used interchangeably in laminated glass elements but the later is more attractive for being used in finite element models. The technique is validated by experimental tests carried out on laminated glass beams at different temperatures.